2020
DOI: 10.1080/0309877x.2020.1813264
|View full text |Cite
|
Sign up to set email alerts
|

Learning from contrasts: first-year students writing themselves into academic literacy

Abstract: The contribution of this article is to highlight how exploring various writing genres in the beginning of higher education can contribute to academic literacy. While many studies have addressed the transition into academia by focusing on academic writing, the use of various writing genres has scarcely been researched. Based on the thematic analysis of focus-group interviews that explore first-year students' experience of writing in academia, we present and discuss three emerging themes: 1) academic writing as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
8
0
3
Order By: Relevance
“…overall, the results of these studies suggest that literacy practices and interactions between teachers and students help students acquire the literacies required to succeed in academia. The second group includes those studies which investigate the role of genre in students' academic literacy development and their socialization into their discourse communities (Andrew & Romova, 2012;Hedgcock & Lee, 2017;Roald et al, 2021). These studies confirm that explicit teaching of academic genres has a positive role in helping novices to acquire academic literacy to flourish in their disciplines.…”
Section: Literature Reviewmentioning
confidence: 90%
“…overall, the results of these studies suggest that literacy practices and interactions between teachers and students help students acquire the literacies required to succeed in academia. The second group includes those studies which investigate the role of genre in students' academic literacy development and their socialization into their discourse communities (Andrew & Romova, 2012;Hedgcock & Lee, 2017;Roald et al, 2021). These studies confirm that explicit teaching of academic genres has a positive role in helping novices to acquire academic literacy to flourish in their disciplines.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Regarding the first theme, genre shift, the results showed that most students had difficulty changing perspective from a science to a popular science approach (Fahnestock, 1986). Within a research-based teacher education, students usually write within the scientific genre (Roald et al, 2020). However, popular science is different.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the text materials follows a similar pattern, in which students who made normative guides wanted to highlight their topic and inform teachers of their findings. Some students also preferred normative guides because they had previously made research presentations for master's thesis seminars and, therefore, it was easier to take the scientific route (Roald et al, 2020). Furthermore, students who were successful in switching genres were able to use their theoretical knowledge to create ready-to-use material and thus succeed in communicating their results to a wider context (Parkinson & Adendorff, 2004;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Writing skill is widely recognized as important in language learning, particularly in developing students' academic literacy in higher education (Pirttimaa et al, 2015;Roald et al, 2021). of several types of writings, argumentative writing skill is typical for EFL learners in this tertiary level across different disciplines (Noroozi et al, 2018;Luna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%